Model Pemberdayaan Dan Komunikasi Organisasi Karang Taruna Desa Munggugianti Kecamatan Benjeng - Linda Nur Fitria; Hisnuddin Lubis (DIMENSI - Jurnal Sosiologi, 2022)
The Karang Taruna's role in the community necessitates a high level of expertise and cooperation with the government. This necessitates empowering and enabling efficient organizational communication models between members and the village government so that development planning initiatives, notably social welfare, can run in harmony. It is done in Karang Taruna in Munggugianti Village, Benjeng District, through studying, discussing, advising, instructing, and mentoring the younger generation. These services address an individual's cognitive, emotional, and psychomotor aspects. Organizational communication has been modeled under the Stephen P. Robbins approach. The findings suggest that the Karang Taruna have a sense of their dignity and are aware of historical patterns that can be used as a learning tool. A second benefit was that Karang Taruna Munggugianti Village residents could air their views in public. As the Village Government's Social-Economic Recovery Partner, the karang taruna Munggugianti Village has the same perception or knowledge of the karang taruna Optimization Strategy. This karang taruna village can create the Independence program, which is part of the activity idea, and put it into action. "Y" communications model is used in the Karang Taruna Munggugianti Village's organizational communications model because it is flexible enough to adapt to any given situation or condition in which it is applied. In the Karang Taruna Munggugianti Village, the wheel communication model, in which the chairman is the center communicator, is the prevalent organizational communication paradigm.